2016
DOI: 10.1037/pst0000032
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of group treatments for posttraumatic stress disorder.

Abstract: Presented herein is a comparative study of group treatments for posttraumatic stress disorder (PTSD). In this study, an emerging intervention, memory specificity training (MeST), was compared with cognitive processing therapy (CPT) using standardized outcome measures of target symptoms (i.e., anxiety and depression from client perspective; memory specificity from independent rater perspective) and global functioning (independent rater perspective), as well as a process measure of expectancy (client perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
0
24
0
4
Order By: Relevance
“…MeST has been shown to lead to significant improvements in the retrieval of specific memories that is sustained over time [20][21][22][23]. Crucially, it also produces significant reductions in depressive symptoms in clinical samples [21][22][23][24]. Recently, a computerised format of MeST (c-MeST) has been developed, which provides an easily accessible, low cost option for improving memory specificity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…MeST has been shown to lead to significant improvements in the retrieval of specific memories that is sustained over time [20][21][22][23]. Crucially, it also produces significant reductions in depressive symptoms in clinical samples [21][22][23][24]. Recently, a computerised format of MeST (c-MeST) has been developed, which provides an easily accessible, low cost option for improving memory specificity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent studies a fifth [16,25] and sixth session [26] were introduced where participants were invited to conduct exercises based on the STOPmodel; they were instructed to think back and write down when they were thinking at an overgeneral level, describe which specific event prompted the overgeneral thinking (as detailed as possible) and come up with and write down an opposite example. Two other new elements were added: a revision and take-home-message in the last session and in the last session homework exercises are provided so participants can continue to train further.…”
Section: Memory Specificity Training (Mest)mentioning
confidence: 99%
“…MeST was found to lead to an increase in memory specificity and improvements in associated cognitive processes (problem solving, rumination and hopelessness) in 10 depressed female inpatients. Although many existing MeST trials have methodological limitations and do not always show positive effects on symptomatology, subsequent investigations with MeST have shown positive results indicating that memory specificity is modifiable and such modification in turn affects the symptoms of emotional disorders and other cognitive processes (such as rumination) that mediate the association between rAMS and emotional disorder [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of these reviews reported that no studies have yet examined the impact of a memory‐therapeutic intervention among people with BD. One intervention, Memory Specificity Training (MeST) (Raes, Williams, et al, ), is regarded as a promising method for improving memory specificity and remediating related symptoms and processes in UD (Eigenhuis, Seldenrijk, Schaik, Raes, & Oppen, ; Raes, Williams, et al, ; Werner‐Seidler et al, ), PTSD (Maxwell et al, ), and Schizophrenia (Blairy et al, ; Ricarte, Hernández‐Viadel, Latorre, & Ros, ). A recent meta‐analysis confirms these effects (Barry et al, ) and concluded that MeST has also been found to improve other processes associated with rAMS, such as deficits in problem solving, future‐oriented thinking, and hopelessness.…”
Section: Introductionmentioning
confidence: 99%